First Autochthonous West Nile Lineage 2 and Usutu Virus Infections in Humans, July to October 2018, Czech Republic - Zelená, Hana; Kleinerová, Jana; Šikutová, Silvie; Straková, Petra; Kocourková, Hana; Stebel, Roman; Husa, Petr; Husa, Petr; Tesařová, Eva; Lejdarová, Hana; Šebesta, Oldřich; Juráš, Peter; et al. (Pathogens (Basel, Switzerland), 2021)
We present epidemiological, clinical and laboratory findings of five Czech patients diagnosed with autochthonous mosquito-borne disease-four patients with confirmed West Nile virus (WNV) and one patient with Usutu virus (USUV) infections, from July to October 2018, including one fatal case due to WNV. This is the first documented human outbreak caused by WNV lineage 2 in the Czech Republic and the first record of a neuroinvasive human disease caused by USUV, which illustrates the simultaneous circulation of WNV and USUV in the country.
Keywords: Usutu virus; West Nile virus; human; mosquito-borne infections